2009
DOI: 10.1007/s11205-009-9515-9
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality of the Chinese Positive Youth Development Scale: Confirmatory Factor Analyses

Abstract: Chinese adolescents, Positive youth development, Confirmatory factor analysis, Chinese Positive Youth Development Scale,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
125
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(129 citation statements)
references
References 37 publications
3
125
0
1
Order By: Relevance
“…Previous research demonstrated that this scale had sound psychometric properties (Shek and Ma 2010Shek and Ma 2014a, b). The 44-item instrument included 15 subscales, including bonding, resilience, social competence, recognition for positive behavior, emotional competence, cognitive competence, behavioral competence, moral competence, self-determination, self-efficacy, clear and positive identity, beliefs in the future, prosocial involvement, prosocial norms, and spirituality.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous research demonstrated that this scale had sound psychometric properties (Shek and Ma 2010Shek and Ma 2014a, b). The 44-item instrument included 15 subscales, including bonding, resilience, social competence, recognition for positive behavior, emotional competence, cognitive competence, behavioral competence, moral competence, self-determination, self-efficacy, clear and positive identity, beliefs in the future, prosocial involvement, prosocial norms, and spirituality.…”
Section: Methodsmentioning
confidence: 90%
“…In this paper, students' PYD competences, life satisfaction and thriving were assessed. To further understand the impact of the program, we adopt the hierarchical approach by assessing the changes in four composite scores (i.e., secondary factor of PYD attributes) which were derived from multi-group confirmatory factor analyses (Shek and Ma 2010). This approach helps us understand the complex nature of service from participants' perspective (Martínez Caro and Martínez García 2007) and was supported by empirical research (Lu et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Based on factor analyses, Shek and Ma (32) These four composite indicators were used to assess participants ' positive youth development in the present study. Scores of the four indicators all range from 1 to 6 with higher scores representing high competences in the constructs.…”
Section: Chinese Positive Youth Development Scale (Cpyds)mentioning
confidence: 99%
“…Using multigroup confi rmatory factor analyses (MCFA), Shek and Ma (21) showed that the 15 basic dimensions of the CPYDS could be subsumed under four higher-order factors, including cognitive-behavioral competencies (CBC), prosocial attributes (PA), positive identity (PID), and general positive youth development qualities (GPYDQ). Evidence of factorial invariance in terms of confi guration, fi rst-order factor loadings, second-order factor loadings, intercepts of measured variable, and intercepts of fi rst-order latent factor, was found.…”
Section: Instruments the Chinese Positive Youth Development Scale (Cpmentioning
confidence: 99%